The relationship between monetary rewards and job satisfaction among administrative personnel at selected public schools in Dungun district, Terengganu / Nor Azizah Salleh - Salleh, Nor Azizah (Faculty of Business and Management, 2019)
The purpose of this correlational study was to analyse the relationship between monetary rewards and job satisfaction among administrative personnel at selected public schools in Dungun District. Terengganu. 43 respondents completed the survey questionnaire which was adopted from Minnesota Satisfaction Questionnaire (MSQ) (1967) and Robles (2018). This study used the population as the respondents and the response rate was 100%. SPSS V-22 was used to analyse the questionnaires in order to determine the result. Most of the respondents were from Sekolah Menengah (SM) Imtiaz Dungun with grade position of N19 and have 15 to 20 years working experience. There was very strong positive relationship between monetary rewards and job satisfaction among administrative personnel at selected public schools in Dungun District. Terengganu (r=0.84, p=0.00). The findings showed that the correlation was significant as a result for allowance (r=0.83, p=0.00), salary (r-0.80, p=0.00) and bonuses (=0.73, p=0.00). Generally, administrative personnel's satisfaction was at highly satisfied (M=4.0I, SD=0.71). Majority of the respondents also perceived that they satisfied with their works and believed that they have secured jobs. It was recommended that the organization increase salary for employees and consider more allocation for bonuses and allowance. Future study should consider other industry and cover a larger range of area in order to gain a more comprehensive and significant result of analysis.